Novel Multi Levels Tool Based on Rotating Ballizing Technique to Manufacturing the Externally Toothed Components an Experimental Study - Abd-Elhalim, Eman S. M.; Fahmy, Emad A.; El-Sheikh, Mohamed N.; Abu-Oqail, Ahmed M. I.; Elmetwally, Hammad T.; Abd-Eltwab, Ayman Ali (Manufacturing Technology Journal, 2025)
Externally toothed components have a very crucial and essential role in all areas of production and manufacturing because they function as away of transmitting motion, energy, and power in all indus-trial applications, such asmodes of transportation, aviation, aerospace, equipment, and operating machines like lathes and milling. All machines have a gear box. Therefore, it is receiving increasing attention. This research presents a new multi-stage rotary ballizing technology for producing toothed parts in one stroke. This process has been investigated experimentally. The parameters that were ex-amined experimentally was at the optimal conditions for single stage ballizing were: die rotation speed of 315 rpm; Axial feed rate, 0.13, mm/rev; The interference (cross in-feed) between the balls and the tubular specimen of 5.5 and 6.5 mm is formed by three stages of ball forming of graduated outer diameters and fixed on a single mandrel; Initial tube thickness is 7 and 8 mm. The effect of these parameters on the forming load, filling ratio and quality of the formed part was studied. The finding sindicated that the seideal variables influence the forming load, tooth filling proportion, and product quality. Experimental results proved the success of this novel technique to form toothed tubular components
Keywords: Multi-stage ballizing; Externally-toothed parts; Ball spinning; Ballizing; Mathematical model; Shear spinning; Coining; Spinning; Gears; Process parameters